The effectiveness of mindfulness-based compassion therapy on psychological well-being and life expectancy in female with multiple sclerosis - Rajaei, Somayeh; Sadrposhan, Najmeh (International Journal of Education and Cognitive Sciences, 2022)
The aim of this study was to evaluate the effectiveness of mindfulness-based compassion therapy on psychological well-being and life expectancy in female with multiple sclerosis. The present study was a quasi-experimental and the statistical population included female with multiple sclerosis in Isfahan in 1399. Sampling was available as 30 patients were selected and randomly divided into experimental (n = 15) and control (n = 15) groups. In this study, Schneider Life Examination Questionnaire (1991) and Reef Psychological Well-Being Scale (1989) were used. Mindfulness-based compassion treatment based on the book Fallah and Ayoubi (1397) was performed in 8 virtual 90-minute sessions. All collected data were analyzed using SPSS 21 descriptive and inferential statistics. The results showed that mindfulness-based compassion therapy had an effect on psychological well-being and its dimensions and life expectancy and dimensions in female with multiple sclerosis. Therefore, mindfulness-based compassion treatment can be an effective treatment for patients with multiple sclerosis.